Realization of time by personality on its way to psychological health - Terletska, L.; Matsionova, Yu. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The analysis of concepts of consciousness, self-consciousness and it’s structure, the borders of process of realization, the realization of time and perception of time are given in the article. The determination of maintenance of concept of notion realization of time, it’s place in the process of self-consciousness, the features of perception of time by personality became the aim of the research. Time is a separate problem that requires independent analysis, reflection, and study. The most important question is the nature of time. Domestic psychologists are more often guided by a linear model of time, its asymmetry, which is related to the passage of time from the past through the present into the future. The characteristics of time include absolute time and relative time, linear and cyclic time models, the direction of time and its reversibility, symmetry, and asymmetry. The degree of their development is uneven. Such a characteristic of time as an inevitability is considered. As it is possible to return to a specific space, it is impossible to return at a particular time. Establishing an objective order or irreversible sequence of events over time implies the disclosure of a causal relationship between them. This is the basis for a person's awareness of the series of events. In order to reveal the causal dependence of events, it is necessary to establish an objective order or an unambiguous, irreversible sequence of events in time. The understanding causal relationship, we indirectly resolve the issue of the aim sequence of events. It is noted that the perception of time, unlike the perception of space, has a fixed starting point from which the reference is made. The starting point is the present, which divides time into the past and the future. Thus, in the perception of time, a man distinguished two aspects: subjective and objective-conditional. The individual element is related to the personal assessment of events, filled with given events and emotions. The objective-conditional item is associated with the objective course of events and their sequence. The subjective aspect creates a reflection of a personal sense of time, while the objective-conditional helps the person to navigate in time.
Keywords: self-consciousness; consciousness; structure of self-consciousness; realization of time; perception of time